Analysis of Composite Panels of Profiled Steel Sheet with Ferrocement by Using Finite Element Method - Mohammed; Nabeel (University of Thi-Qar Journal, 2021)
This paper concerns with the application of finite element technique to the nonlinear analysis of the behavior of profiled steel sheet ferrocement (PSSF) composite panels. The composite panels were analyzed using nonlinear three dimensional finite element models. The constitutive models of the nonlinear material behavior for ferrocement matrix, PSS, and steel wire mesh were used. ANSYS version 16.1 program code was used to analyze the three dimensional model. Ferrocement was modeled by using the 8-noded isoperimetric brick elements (SOLID65) with three degrees of freedom, while the profiled steel sheet was modeled as SHELL181 element with four-node element with six degrees of freedom at each node: translations in the x, y, and z directions, and rotations about the x, y, and z-axes. A nonlinear spring element, COMBIN14, was used to represent the mechanical connectors, while to simulate the adhesive epoxy layer solid element SOLID185 was used. It was defined by eight nodes having three degrees of freedom at each node: translations in the nodal x, y, and z directions. The wire mesh reinforcement was modeled as a volume ratio distributed within the ferrocement brick elements. The analytical results of load-deflection response have been compared with available experimental works.